Increased solubility and functional properties of precipitated Alfalfa protein concentrate subjected to pH shift processes. (October 2021) - Nissen, Signe H.; Schmidt, Jesper M.; Gregersen, Sandra; Hammershøj, Marianne; Møller, Anders H.; Danielsen, Marianne; Stødkilde, Lene; Nebel, Caroline; Dalsgaard, Trine K.
Abstract: Protein fractionated from alfalfa exhibits promising properties for exploitation as food ingredient. However, further knowledge and improvement of the functional properties is essential to increase the potential for commercial use. This might be obtained by acid or alkaline pH shift processes. The effect of pH shifting compared to controls (buffer solutions) at different pH-values were investigated concerning protein solubility, foamability, and gelation. The effect of salt (NaCl) concentration was also studied. At pH 12, more cross-linkages were observed as lysinoalanine, lanthionine and also conversion of L-Ser to D-Ser was highest at pH 12. Therefore, the pH-shift method with pH 11 was chosen for further investigation, which increased the solubility from 50% to 70–80%. The alkaline pH shift (pH 11) increased the foam overrun and stability, where pH 7 reached the highest stability with >60% foam volume remaining after 1 h. The protein gel strength showed remarkable potential with the alkaline pH shift method with re-adjusting to pH 7, reaching 2584 Pa with 72 g/L protein. For the acid pH shift with re-adjustment to pH 2 followed by pH 3, the foam overrun increased to 140% and protein solubility to 57% at low protein concentration (2 g/L). Addition of salt (185 mM NaCl) increased the foam overrun at pH 5 and 7 for all samples. Overall, these results indicated that prior alkaline pH treatments and salt can increase the potential of alfalfa protein in terms of certain functionality in foods. Graphical abstract: Image 1 Highlights: A pH of 11 for alkaline pH shift was chosen as it maintains the protein quality. Alkaline pH shift increases solubility, foamability and gelation of alfalfa protein. Acid pH shift increases foam overrun and solubility at low protein concentration. Addition of salt increases alfalfa protein foam overrun at pH 5 and 7.